Pomelo juice-Drug interactions: A word of caution - Greeshma V Shetty; P N Girish; K P Gopalakrishna Rao; Ashok Menon (Wolters Kluwer Medknow Publications, 2023)
The main of this article is to study the interactions of certain commonly used drugs with pomelo juice which is commonly consumed as easily available fruit or fruit juice in certain parts of India. Relevant literature was identified by searching PubMed and other articles on the web. Various search words which were used are "Grapefruit," "pomelo," "drug interactions," and "juice-drug interactions." Inclusion criteria included grapefruit juice-drug interaction studies and pomelo juice-drug interactions. Exclusion criteria were articles actually irrelevant to the juice-drug interaction topics. After reviewing the summary of each article, few articles were directly excluded because of actually irrelevant topics. Finally, eight articles were selected as reference articles and certain data were obtained and our opinion about the same is mentioned in the present article. The full text of each included article was critically reviewed, and valuable information was summarized by data interpretation. Pomelo "(Citrus maxima/Citrus grandis)" is the largest citrus fruit from the family Rutaceae and the principal ancestor of the grapefruit. It is a natural, nonhybrid citrus fruit native to Southeast Asia. Pomelo is commonly consumed and used for festive occasions throughout Southeast Asia. It has also been found to have drug interactions similar to grapefruit. The fruit is large, 15-25 cm in diameter, and weighing 1-2 kg. It has a thicker rind than the grapefruit and is divided into 11-18 segments. Pomelo is closely related to grapefruit and extensively studied and contains furanocoumarins which have been identified as inhibitors of cytochrome P450 3A4 in grapefruit juice in vitro. The fruit was first described in 1750 by Griffith Hughes, and in 1789, Patrick Browne referred to it as "forbidden fruit" or "smaller shaddock." Its taste also varies from sour or bitter to sweet. The fruit is nearly round or slightly pear shaped in clusters similar to grapes, 10-15 cm wide with smooth, finely dotted peel, up to 1 cm thick. The pulp is yellow or pink to red, which has 11-14 segments with thin membrane. The fruit is very juicy. The fruit presents with pointed seeds about 1.25 cm in length. In Karnataka, a type of pomelo named Devanahalli pomelo (Gi registered) is exclusively grown in the region around Devanahalli taluk, Bangalore, as an exotic crop variety. It is locally known as chakkota. Besides, pomelo has many names such as batabi lebu or jambura in Bengali and chakotra in Hindi-speaking states. In the present pandemic outbreak, in-home consumption of packaged fruit juices has increased among people in the cities, whereas in-home consumption of easily grown and easily available fruits such as pomelo, grapes, apples, and their juices has increased among people in the villages. Hence, caution is required while consuming pomelo juice (similar to grapefruit juice) with certain drugs.